Health financing analysis in the implementation of minimum service standards in Lumajang Regency - Risdiyanti, Arie; Paramu, Hadi; Sunarto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Health financing in Lumajang is still far from the target. Therefore, a study focused on the implementation of minimum service standards (MSS) in the health sector is needed. Despite the government emphasis on MSS health, disparities in service access and health conditions persist.Objective: To provide insights into the effectiveness of health financing, serving as a foundation for policy recommendations to enhance the efficiency and effectiveness of health fund allocation in Lumajang Regency.Methods: The study employed a quantitative approach, utilising district health accounts (DHA) and cost and benefit analysis (CBA). The budget allocation for different MSS health services was also investigated. The analysis involved examining the spending proportion relative to total health expenditure. The study design used a qualitative descriptive method. The data source was obtained from the budget realisation report for the MSS health sub-activities at the Community Health Center (CHC) and the Lumajang Health Office. Data analysis was performed by an integration of DHA and CBA approaches. We performed mapping costs and benefits analysis and calculated the sensitivity of financing to whether it is economically profitable and provides leverage for achieving MSS performance indicator targets. Results: The realisation of local original revenue in the health sector tended to fall below targets. Central transfer funds dominated the funding sources in CHC. The highest health budget allocation of MSS was received by maternal health services, while other services only received a proportion relative to a decrease in total health expenditure.Conclusion: In Lumajang Regency, analysis of the costs and benefits of regional health financing to fulfil MSS health showed that the benefit-cost ratio (BCR) value was > 1, meaning that health financing for MSS in the District Health Sector was profitable, so it should be used as a regional priority program in overcoming regional health problems.